Research progress on biomarkers of diabetic nephropathy - ZHAO Qingqing, CHENG Xiaoliang (Jichu yixue yu linchuang)
Diabetic nephropathy (DN) is one of the most common complications of diabetes, and has become the main cause of chronic kidney disease and end-stage renal disease worldwide. At present, the pathogenesis of DN is not completely clear. For a long time, the routine treatment of DN is a combination of life management, hypoglycemic, hypotensive with other symptom-based treatment, but its progress cannot be delayed. Therefore, early detection, diagnosis, and treatment of DN are particularly important, but there is currently no single indicator that can be used for early diagnosis of DN. Therefore, the development of simple, sensitive, and efficient biomarkers is becoming increasingly important.